Starotestamentalny kontekst opisów cudownych uwolnień z Dziejów Apostolskich - Conder, Zbigniew (My University, 2016)
Praca podkreśla myśl teologiczną zawartą w Dziejach Apostolskich poprzez porównanie odniesień do motywu przewodniego cudownego uwolnienia z sytuacji uwięzienia, użytego w różnych tekstach biblijnych. Wiadomo powszechnie, że autorzy w swoich dziełach odwołują się do słów kluczowych, aby podzielić się swymi emocjami i przekonaniami o swojej wierze. Znajomość praw krytyki literackiej, starożytnej historii i zasad opisanych przez Magisterium do prawidłowego czytania tekstów biblijnych pozwala odróżnić elementy gatunku literackiego używane przez autora biblijnego od głównego przedmiotu nauczania zawartego w tekście. Na kartach Dziejów Apostolskich opisane zostały powtarzające się próby, podejmowane przez władze wrogie Kościołowi, aby zastraszyć wyznawców Chrystusa. Niniejsza praca porównuje je z opisami zawartymi w księgach Starego Testamentu. Uwzględnia różnorodność kontekstu, a zarazem dostrzega podobieństwa do biblijnych opisów doznań Józefa z Księgi Rodzaju, następnie trzech młodzieńców i proroka z Księgi Daniela. Odnotowuje aluzje w słownictwie i stylu narracji prowadzonej przez autora Dziejów Apostolskich; przede wszystkim, podkreśla jako zamiar autora wyakcentowanie prymatu wiary w Boga i mocy świadectwa wiary sług Bożych. Pokazuje wreszcie jak motyw uwolnienia Piotra, Jana, Pawła i Sylasa z więzienia służy szerzeniu słowa Bożego i rozwojowi Kościoła.

The work highlights the theological ideas contained in the Acts of the Apostles through the comparison between some approaches to the leitmotif of miraculous liberation from prison used in the various biblical texts. It is well known, that writers use keywords to share theirs emotions and convictions about their faith. Knowledge of the laws of literary criticism, the ancient history and the principles inculcated by the Magisterium for the proper reading of biblical texts is enough to distinguish between the elements of the literary genre used by the author and the subject of the teaching of the main text. Along the Acts of the Apostles are described some repeated attempts made by the authorities hostile to the Church to intimidate the followers of Christ. This research then compares the Acts of the Apostoles with the books of the Old Testament. However, it does not forget the overall environment and as the sometime, mainly sees similarities with the biblical descriptions of Joseph’s life in Egypt from the book of Genesis, then the life test of the three young people from the fiery furnace and the fidelity of the prophet from the book of Daniel. The work has notices the allusions in the vocabulary and style of narration created by the author of the Acts; above all, his will of emphasizing the primacy of the faith in God. It emphasizes the intention of the author to show the power of faith and the testimony of the servants of God. Then it is showed, that the liberation of Peter, John, Paul and Silas from jail is displayed to strengthen the Church and spread the word of God.
The Old Testament’s context of the descriptions of the miraculous liberations in the Acts of Apostles
Wydział Teologiczny
Keywords: Patriarcha Jakub; Joseph Patriarch; Daniel; Piotr; Peter; Paweł; Paul